KINERJA GURU PROFESIONAL (GURU PASCA SERTIFIKASI) - Kartowagiran, Badrun (Jurnal Cakrawala Pendidikan, 2015)
Abstract: Professional Teachers’ Post-Certification Performances. This study aims to investigate professional teachers’ post-certification performances. It was an evaluation research study employing the goal-free evaluation model by Scriven. The sample, selected from a population of 548 teachers who have received professional incentives Sleman Regency, comprised 55 teachers (5 from kindergartens, 28 from elementary schools, 13 from junior high schools, 7 from senior high schools, and 7 from vocational schools), principals, and staff members of the Office of Education of Sleman Regency. The data were collected through questionnaires, interviews, focus group discussions, documents, and assessment sheets, and were analyzed using quantitative and qualitative descriptive techniques. The results show that the post-certification performances of the majority of professional teachers are not satisfactory yet, shown by the fact that of the 17 indicators, 7 indicators are good and 10 other indicators are fair. Keywords: teacher performance